Rancangan Elemen Fisik Kampung Tematik Tempo Doeloe Jagalan sebagai Destinasi Wisata - Dewi, Diah Intan Kusumo; Maharani, Edelways Tiara; Mahardika, Putri Prabani; Nurini, Nurini; Dewi, Santy Paulla (Jurnal Riptek, 2022)
Productive Thematic Village is one of the priority activities carried out by the Semarang City Government as a solution in improving community welfare. Thematic Village is based on regional potential and the community as the subject of the Thematic Village plays an active role in improving welfare. One thematic village that has potential as a tourist destination is the Kampung Tempo Doeloe which is located in Jagalan Village. Kampung Tempo Doeloe was initiated by the local kelurahan government as an effort to preserve ancient buildings and existing traditions. However, in its continuation as a Thematic Village itself, this village still has problems. Therefore, a design is needed for the sustainability of thematic villages and the transformation of thematic villages into tourist destinations. The purpose of this study is to provide recommendations for the design of Kampung Tempo Doeloe which focuses on physical elements. Data collection methods used in this research are field observations, interviews, institutional surveys and document review. Analytical method used is descriptive qualitative in the form of descriptive comparative method. The results of this study are recommendations of Â physical elements design which divided into 5 elements, namely Circulation and Parking, Open Space, Signages, Supporting Activities, and Preservation.. This recommendation is expected to be an input and consideration for the Semarang City Government in developing and transforming thematic villages into tourist destinations.Â